2018
DOI: 10.1159/000491664
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization Leucine-Rich-Repeat Protein 1 Deficiency Protects Against Cardiac Hypertrophy by Pressure Overload

Abstract: Background/Aims: Nuclear localization leucine-rich-repeat protein 1 (NLRP1) is a cytoplasmic protein, involved in autoimmune diseases, mammalian reproduction, neuronal cell death, and stroke. However, the role of NLRP1 in cardiac hypertrophy remains unclear. We used in vivo and in vitro models to investigate the effects of NLRP1 on cardiac hypertrophy. Methods: We used NLRP1-deficient mice and cultured neonatal rat cardiomyocytes with gain and loss of NLRP1 function. Cardiac hypertrophy was estimated by echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Transthoracic echocardiography and haemodynamic analysis were used for detection as previous study described. 15…”
Section: Echocardiographic and Haemodynamic Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Transthoracic echocardiography and haemodynamic analysis were used for detection as previous study described. 15…”
Section: Echocardiographic and Haemodynamic Evaluationmentioning
confidence: 99%
“…Cardiac morphology and histomorphometric analysis were performed as previous study described. 15 Haematoxylin and eosin (H&E) staining was used to count cell surface area with more than 200 cells per group. Picrosirius Red (PSR) staining was used to count LV collagen volume with more than 10 fields for each heart.…”
Section: Cardiac Morphology and Histomorphometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…PE signaling pathway plays an important role in cardiac hypertrophy, which activates a series of downstream signal events, including activation of NFAT3 nuclear translocation and activation of the three best-characterized mitogen-activated protein kinase (MAPK) subfamilies, namely p38, JNKs and ERKs [22,23]. In order to detect the effect of Sop on MAPK or NFAT3 signal pathway, we treated NRCMs with Sop at different concentrations (10 or 50 μM) for 48 h. Immunoblotting indicated that Sop had no effect on phosphorylation levels of (p38, JNK, ERK) and NFAT3 nuclear translocation (Supplementary Figure S5A,B).…”
Section: Sop Enhances the Decreased Autophagy In Pathological Cardiac Hypertrophymentioning
confidence: 99%
“…Vol.62: e19180699, 2019 www.scielo.br/babt hypertrophy[21,22]. ERK1/2 is a group of protein kinases, which are distributed in the cytoplasm with the function of both serine and tyrosine phosphorylation.…”
mentioning
confidence: 99%